Plastination of Human Limb Sections in Bangladesh: Entering a New Era of Body Preservation - Rahman, Md Moshiur; Riad, Md Riadul Zannat; Amin, Nahid Farhana (Bangladesh Journal of Anatomy, 2020)
Introduction: Plastination becoming popular worldwide in teaching-learning of Anatomy. Scarcity of donated bodies in the medical colleges of Bangladesh is a major problem which may be solved to some extent with the plastinates. Materials and Methods: Fifteen sections of human limbs were plastinated in Bangabandhu Sheikh Mujib Medical University (BSMMU). The previously embalmed sections were prepared by 50% ethanol and dehydrated with graded series of acetone at -25°C in a deep freezer. Forced-impregnation was done with S10 silicone at -25°C and gas-curing was done within a curing chamber by S6. Results and Discussion: The specimens were dry, odorless, fumeless and easy to handle. Some sort of shrinkage and distortion was observed in the specimens. Conclusion: Current attempt may be a crucial point in the history of body preservation and teaching-learning of Anatomy in Bangladesh. Bangladesh Journal of Anatomy July 2020, Vol. 18, No. 2, pp. 47-54